2015
DOI: 10.15561/18189172.2015.12015
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of junior school age children’s posture disorders

Abstract: Purpose: to describe specificities of early diagnosis method for junior school age children's posture disorders. Material: in pedagogic experiment 156 junior school age children (boys and girls of 7-10 years' age) participated. All children had no experience of training in sport circles. For determination of uniformity of the tested we fulfilled experts' examination for presence or absence of external signs of posture disorders in frontal plane. The children's examination was conducted by qualified specialists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…All these reduce indicators of schoolchildren's general health level. That is why it is necessary to support by all means and develop schoolchildren's motor fitness (Ivashchenko, & Yermakova, 2015a, 2015bBliznevsky et al, 2016;Pomeshchikova et al, 2016). It should be noted that in every age period posture has its own peculiarities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these reduce indicators of schoolchildren's general health level. That is why it is necessary to support by all means and develop schoolchildren's motor fitness (Ivashchenko, & Yermakova, 2015a, 2015bBliznevsky et al, 2016;Pomeshchikova et al, 2016). It should be noted that in every age period posture has its own peculiarities.…”
Section: Introductionmentioning
confidence: 99%
“…It was proved that prophylaxis measures are purposeful only at early stages of in work of muscular system. Traditional approach in the form of prophylaxis examination can not give confident information about initial stages of child organism's muscular work imbalance (Razumeiko, 2015b). It is important to substantiate selection of adequate tests (Khudolii, Iermakov, & Prusik, 2015;Khudolii, Iermakov, & Ananchenko, 2015) and pedagogic control over schoolchildren's motor qualities (Ivashchenko, Yermakova, Cieslicka, & Muszkieta, 2015;Ivashchenko, Yermakova, Cieślicka, & Śukowska, 2015;Ivashchenko et al, 2016).…”
mentioning
confidence: 99%
“…Diagnostic of torso showed that 63% of schoolchildren have disorders. It witnesses about early symptoms of posture abnormalities (Kupreenko, 2015; Nosko, Razumeyko, Iermakov & Yermakova, 2016; Razumeiko, 2015).…”
Section: Introductionmentioning
confidence: 99%